Natural pozzolana of micro and nano-size as cementitious additive: resistance of concrete/mortar to chloride and acid attack. Issue 1 (1st January 2021) - Al-swaidani, Aref M.
Abstract: The goal of the current paper is to study the effect of natural pozzolana (NP) when ground to a micro and nano size on some concrete properties. Syria is rich in natural pozzolana with an estimated quantity of nearly 1 billion tonnes. Four properties, namely compressive strength, chloride permeability, chloride-induced reinforcement corrosion and acid attack on mortar, have been investigated. Six levels of micro-NP (from 0% to 50%), and nano-NP (from 0% to 5%) were added as cement replacement to produce the studied concrete/mortar mixtures. The results revealed that grinding NP to extremely fine particles has positive effects. The shortcoming related to the lower early compressive strength can be eliminated. Further, much lower chloride permeability and longer corrosion initiation times were clearly observed in the concrete containing nano-NP. The best results were obtained when NP was added at 30% or more at micro-scale and at 3–4% at nano scale. Furthermore, acid resistance particularly at the early ages of exposure was noticeably improved with such additives. SEM technique fitted with EDX analysis was employed in the current research to study the microstructure of the cement paste after being exposed to acid solutions. XRD and TGA techniques were used as well.